Dari Paskah Yahudi ke Ekaristi: Tinjauan Historis-Teologis - Irwan, Irwan; Marianus Dinata Alnija; Shelomita Selamat; Marseli, Madalena (Pusat Riset dan Inovasi Nasional, 2024)
The Eucharist has a deep meaning; understanding this will help Catholics to live it more deeply. One of the meanings of the Eucharist can be explored by knowing that the Eucharist has its roots in the Jewish Passover tradition. This article aims to discuss the historical and theological relationship between the Jewish Passover tradition and the Eucharist in the Catholic Church. The method used is a literature study. The article explains that the Eucharist has its roots in three main concepts of the Jewish tradition: heavenly manna, the bread of the Divine presence, and communion. These meanings can contribute to increasing the awareness and faith of the people in celebrating the Eucharist.